2014
DOI: 10.1002/embj.201488126
|View full text |Cite
|
Sign up to set email alerts
|

Capping of the N-terminus of PSD-95 by calmodulin triggers its postsynaptic release

Abstract: Postsynaptic density protein-95 (PSD-95) is a central element of the postsynaptic architecture of glutamatergic synapses. PSD-95 mediates postsynaptic localization of AMPA receptors and NMDA receptors and plays an important role in synaptic plasticity. PSD-95 is released from postsynaptic membranes in response to Ca 2+ influx via NMDA receptors. Here, we show that Ca 2+ /calmodulin (CaM) binds at the N-terminus of PSD-95. Our NMR structure reveals that both lobes of CaM collapse onto a helical structure of PSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
114
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(120 citation statements)
references
References 57 publications
4
114
0
Order By: Relevance
“…To evaluate whether these mutations affected binding of apoCaM we utilized a fluorescence polarization (FP) assay we had adopted earlier for defining CaM binding (52) to evaluate the relative binding-affinities of the WT and mutant α 1 1.2 IQ domains for apoCaM (Fig. 4; Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate whether these mutations affected binding of apoCaM we utilized a fluorescence polarization (FP) assay we had adopted earlier for defining CaM binding (52) to evaluate the relative binding-affinities of the WT and mutant α 1 1.2 IQ domains for apoCaM (Fig. 4; Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…We recently found that Ca 2+ /CaM also binds to the N‐terminal 16 residues of PSD‐95 (Zhang et al , ). We showed by NMR structural analysis that both CaM lobes collapse around a helix formed by PSD‐95 residues 1–14 (Zhang et al , ). This interaction shields two palmitoylation sites (C3 and C5) that are crucial for postsynaptic targeting of PSD‐95.…”
Section: Introductionmentioning
confidence: 99%
“…This interaction shields two palmitoylation sites (C3 and C5) that are crucial for postsynaptic targeting of PSD‐95. Y12 in PSD‐95 makes the most contacts with Ca 2+ /CaM (Zhang et al , ). The Y12E mutation abrogates binding of Ca 2+ /CaM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression analysis suggested that CDKL5 can be localized in postsynaptic structures (7) where RNA interference and mutation analysis showed that it can regulate dendritic spine density and morphology and modulate excitatory synaptic function (8). The synaptic localization of CDKL5 seems to be regulated by its direct interaction with the palmitoylated form of postsynaptic density protein 95 (PSD-95) (9,10), or by the formation of a complex involving PSD-95 and its interacting protein netrin-G1 ligand (NGL-1), a target of CDKL5 kinase activity (8).…”
mentioning
confidence: 99%